Kabut Asap, Ancaman Terhadap Human Security dan ASEAN Way - Yusnarida Nizmi (Jurnal Masyarakat Maritim, 2021)
Forest fires and haze become annual trend phenomena of the failure Southeast asia regional and related institutions in prevention efforts of haze problems. Comprehensive Monitoring and rules enforcement to prohibition forest fires shows how authorized institutions have difficulties and boundaries to punish the land owners who burn the forests, and to stop cleaning land by burning the forest and land. This research describes the causes of haze occur in Southeast asia, the threats of haze pollution and why ASEAN through its ASEAN Way not success yet in solving haze pollution that contributes insecure human security of millions people in this region. This research apply neoliberal institutionalism approach and collect the data from library research. This research shows that in regional level, ASEAN continuesly do cooperation and formulate policies to solve the regional haze problems. In Ministerial Meeting Level, ASEAN has reviewed Regional Haze Action Plan and finally sign the ASEAN Agreement on Transboundary Haze Pollution, an agreement which is binded and ratified all the member of ASEAN. Keywords: Haze, Human Security, ASEAN Way